Key-Specific Structure in Mozart's Music: A Peek into his Creative Process? - Rom, Uri B.; Rosset, Saharon (Empirical Musicology Review, 2023)
Theories of tonal music take for granted that all keys of the same mode (i.e., all major and all minor keys) are employed by composers in essentially the same way; however, newer analytical and cognitive research challenges this view by pointing to aspects of transpositional nonequivalence among the keys. The present study offers possibly the first systematic, data-driven investigation of correlations between the choice of absolute key and structure across a composer's body of works. By performing an extensive corpus-based analysis of music by Wolfgang Amadé Mozart (1756–91), we derive 55 prototypes, subsuming phenomena from three independent domains: dynamic-rhetoric gestures that launch orchestral works, digressions to the parallel minor in sonata-allegro movements, and the occurrences of a particular six-note motive across Mozart's complete oeuvre. Ten prototypes display a significant association with a specific key after correction for multiple comparisons, amounting to a statistically significant total. Investigation of key-related musical structure offers fresh insight into Mozart's compositional decisions and the relation between schemata and their instantiations in his works, at the same time suggesting a revised perspective on traditional key characteristics. Mozart's perfect pitch offers one possible explanation for the role of key-related structure in his works; however, we also contemplate other possible explanations.